2019
DOI: 10.1038/s41598-019-47257-7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo effects of insulin-producing cells generated by xeno-antigen free 3D culture with RCP piece

Abstract: To establish widespread cell therapy for type 1 diabetes mellitus, we aimed to develop an effective protocol for generating insulin-producing cells (IPCs) from adipose-derived stem cells (ADSCs). We established a 3D culture using a human recombinant peptide (RCP) petaloid μ-piece with xeno-antigen free reagents. Briefly, we employed our two-step protocol to differentiate ADSCs in 96-well dishes and cultured cells in xeno-antigen free reagents with 0.1 mg/mL RCP μ-piece for 7 days (step 1), followed by addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…The study demonstrated that intraperitoneal transplantation of 1.5 × 10 6 BM-MSCs that differentiated into IPCs into diabetic rats led to the improvement of the hyperglycemic states. However, in a recent report on the transplantation of IPCs generated from human AT-MSCs with μ -pieces into diabetic mice, 4.8 × 10 7 cells were transplanted under the kidney capsule or intramesentery region and led to normoglycemic states [ 44 , 45 ]. One of these studies also calculated the cell number of generated IPCs and found that 1.8 × 10 4 IPCs were obtained from 5 × 10 5 AT-MSCs, indicating that 3.6% of the initial AT-MSCs differentiated into IPCs; thus, approximately 1.7 × 10 6 IPCs are needed per mouse to gain the normoglycemic states in STZ-induced diabetic mice [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated that intraperitoneal transplantation of 1.5 × 10 6 BM-MSCs that differentiated into IPCs into diabetic rats led to the improvement of the hyperglycemic states. However, in a recent report on the transplantation of IPCs generated from human AT-MSCs with μ -pieces into diabetic mice, 4.8 × 10 7 cells were transplanted under the kidney capsule or intramesentery region and led to normoglycemic states [ 44 , 45 ]. One of these studies also calculated the cell number of generated IPCs and found that 1.8 × 10 4 IPCs were obtained from 5 × 10 5 AT-MSCs, indicating that 3.6% of the initial AT-MSCs differentiated into IPCs; thus, approximately 1.7 × 10 6 IPCs are needed per mouse to gain the normoglycemic states in STZ-induced diabetic mice [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when considering the proper transplantation site, it is proposed that the intra-mesentery transplantation identified in a previous study is one reasonable and less-invasive transplantation site 12 . As professional hepato-biliary-pancreatic and transplant surgeons, the authors routinely undergo high-risk laparoscopic surgeries 3537 .…”
Section: Discussionmentioning
confidence: 99%
“…Generated cells and extirpated organs were prepared and stained by methods already reported 12 . Briefly, generated IPCs were fixed using a cell fixing kit (Funakoshi), recipient mice were sacrificed and IPCs bearing kidneys were extirpated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we focused on ADSCs as a new cell source for IPCs 12,14,15 . We have previously reported a new two-step differentiation protocol 16 and its modification to a more effective xeno-free and three-dimensional culture protocol 17 to generate functional IPCs from ADSCs. For clinical application, it is important to exclude immature IPCs.…”
Section: Introductionmentioning
confidence: 99%